Sepsis secondary to complicated skin and soft tissue infection caused by Ignatzschineria indica. First case report in Latin America - Cipolla, Lucía (2018)
Fil: Cipolla, Lucía. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Bacteriología Especial; Argentina.